The Early Modern Cultures of Neo-Latin Drama - Taylor, Andrew, 1964-; Ford, Philip, 1949-2013 (Book collections on Project MUSE., 2013)
The essays in this collection all illustrate the vitality of Neo-Latin drama in early modern Europe, arising from its productive combination of classical models with deep-rooted vernacular traditions. While the plays were often composed in the context of a school or university setting, the dramatists seldom neglected the need to appeal to a broad audience, including non-Latinists. Yet the use of Latin, and the ambiguity of a plurivocal literary form, allowed the authors of these plays to introduce messages and ideas which could be subversive of the prevailing political and religious authoritie.